Intake of processed meats by Costa Rican women: effect of socioeconomic status: VARIATION BY SOCIOECONOMIC STATUS - Santamaría-Ulloa, Carolina; Bekelman, Traci A. (Revista de Biología Tropical, 2021)
Introduction: Intake of processed meats has been associated with serious health problems that are common among women. In 2015, the International Agency for Research on Cancer classified processed meats as human carcinogens, associated specifically with colon cancer. The increase in intake of processed meats, which are a low-cost source of dietary protein varies by socioeconomic status (SES) and can impact chronic disease incidence. Objective: Examine the association between processed meats intake and (a) total protein intake, (b) inadequate protein intake, by SES. Methods: This study included a representative sample (N = 135) of women age 25 to 45 years, with one to four children, from three different socioeconomic groups who were residents of two counties from the Greater Metropolitan Area of San José, Costa Rica between June 2014 and March 2015. Using photographs, we examined women’s perceptions of the cost and perceived desirability of 12 different foods, including processed meats. Using 24-hour dietary recalls collected on three different days, and the ValorNut food composition database, we estimated total protein intake, in grams, and determined the intake frequency (times/day) of processed meat. Each women’s dietary protein requirement was estimated based on her bodyweight. Inadequate protein intake was calculated as the difference between protein requirement and actual intake. A linear regression model was used to determine the association between total protein intake in grams and intake frequency (times/day) of processed meat. A logistic regression model was used to estimate the association between low protein intake and intake frequency (times/day) of processed meat. Results: Processed meats were perceived as the least preferred protein source but were the third most commonly consumed protein source. Consumption of processed meats differed by SES and was lower in the higher SES group (P < 0.01). The most commonly consumed processed meats by SES were “mortadella” (low-SES), sausages (middle-SES), and sliced turkey/ham (high-SES). Processed meat intake was significantly associated with an increase in protein intake. There was an inverse association between SES and inadequate protein intake. Conclusions: Processed meat intake is associated with SES. Women may consume processed meats because they are perceived to be a low-cost protein source. Educational strategies are needed to help women identify their protein needs and meet those needs with healthier and affordable dietary alternatives.